SQUID detected low-field NMR for the evaluation of internal fruit quality - Van Zyl, Derrick Steven (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.